1974
DOI: 10.1038/bjc.1974.182
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal Irradiation and Childhood Cancer: Causation or Coincidence?

Abstract: A re-analysis of published data from the Oxford Childhood Cancer Survey shows that the frequency of leukaemia and of solid cancers in childhood is greater following antenatal x-radiography, not only in singleton births but also in monozygotic and dizygotic twins. The radiography rate was 10% in singletons and 55% in twins. A similar excess of leukaemia and of solid cancers in the x-rayed with such different rates of radiography is strong evidence for irradiation as the cause. The low observed frequency of mali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
2

Year Published

1975
1975
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(30 citation statements)
references
References 30 publications
1
27
0
2
Order By: Relevance
“…It is true that when the risks are standardized for various epidemiological factors a small reduction in the estimates results; yet this is quite insufficient to " explain " the radiation association completely. Moreover, as pointed out by Mole (1974), the fact that the excess mortality in twins is very similar to that in singletons, despite the very different irradiation rates, militates strongly against the possibility of the x-ray excess being due to selection of pre-disposed cases for x-raying. A genuine causation would be more convincing and perhaps more in line with prior expectations if the irradiated cases exhibited more differences from the unirradiated, especially as regards age and tumour type.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is true that when the risks are standardized for various epidemiological factors a small reduction in the estimates results; yet this is quite insufficient to " explain " the radiation association completely. Moreover, as pointed out by Mole (1974), the fact that the excess mortality in twins is very similar to that in singletons, despite the very different irradiation rates, militates strongly against the possibility of the x-ray excess being due to selection of pre-disposed cases for x-raying. A genuine causation would be more convincing and perhaps more in line with prior expectations if the irradiated cases exhibited more differences from the unirradiated, especially as regards age and tumour type.…”
Section: Discussionmentioning
confidence: 99%
“…However, certain categories have been excluded from the analysis, as follows: (a) cases not traced or matched with a suitable control (27%); (b) adopted children, for whom records of pre-natal irradiation are very rarely available (0.7%); (c) cases found to have benign, dubious or negative pathology (14%); (d) twins, whose pre-natal irradiation rate is very high and who are under-represented among the controls (2.2%) (see Mole, 1974;Stewart, 1973 Lymphatic M 0-6 1-8 4-2 7-4 10-6 13-3 15-5 17-4 18-9 20-2 21-3 22-5 23-6 leukaemia F 0-6 2-0 3-9 6-5 9 0 11-4 13-1 14-5 15-6 16-5 17-4 18-1 18-7 Tot 0-6 1-9 4-1 6-9 9-8 12-4 14-4 16-0 17-3 18-4 19-4 20-4 21-3 Myeloid M 0 5 1-2 1-9 2-8 3-6 4-4 5 0 5-6 6-1 6-6 7-2 7-8 8-4 leukaemia F 0 5 1-2 1 9 2-6 3-1 3-7 4-3 4-9 5-4 5-8 6-4 7 0 7-7 Tot 0 5 1-2 1-9 2-7 3-4 4-1 4-7 5-2 5-8 6-3 6-8 7-4 8-0 Allleukaemias M 2-0 4-7 9 0 14-5 19-7 24-4 28-2 31-5 34-3 36-8 39-2 41-4 43.7 Lymphomata M 0-4 0-8 1-4 2-2 3 0 3-9 4.9 5.7 6-7 7-6 8-4 9-3 10-4…”
Section: Description Of the Data Availablementioning
confidence: 99%
See 1 more Smart Citation
“…Twin studies have been used to eliminate some of the confounding factors [87e89]. Although the reports of Mole [89] and Harvey et al [87] were positive, the Rodvall study [88] was not statistically significant.…”
Section: Human Studies Concerning the Vulnerability Of The Embryo To mentioning
confidence: 99%
“…Boice and Miller [78] have concluded that the more recent data have reduced the discrepancy between these two extreme viewpoints. Based on the reports of Muirhead and Kneale [82] and Mole [89] they believe that 'The risk estimate associated with intrauterine radiation is not substantially greater than that seen following childhood irradiation. ' Doll and Wakeford [90] expressed their opinion about the carcinogenic effect of intrauterine radiation and concluded that 'Irradiation of the fetus in utero increases the risk of childhood cancer, and increases the risk from exposures of the order of 10 mGy, and that in these circumstances the excess risk is w6% per Gy.…”
Section: Human Studies Concerning the Vulnerability Of The Embryo To mentioning
confidence: 99%